Corpus Callosal Abnormalities in Dogs. (19th May 2014) - Gonçalves, R.; Volk, H.; Smith, P.M.; Penderis, J.; Garosi, L.; MacKillop, E.; de Stefani, A.; Cherubini, G.; McConnell, J.F.
<x xml:space="preserve">Abstract</x> Background Corpus callosal abnormalities (CCA) in dogs have been only sporadically reported and are poorly characterized. Hypothesis/Objectives To describe the clinical presentation and magnetic resonance imaging (MRI) characteristics of dogs with CCA. Animals Fifteen client‐owned dogs. Methods Retrospective study. Records of the contributing institutions were reviewed to identify dogs diagnosed with malformations affecting the corpus callosum (CC); cases in which the CCA was thought to be secondary were excluded. Results The most represented breeds were Staffordshire Bull Terriers (5/15) and Miniature Schnauzers (3/15; n = 3, 20%) and the mean age at time of presentation of 19 months (range 3–81 months). The clinical signs most commonly reported were adipsia/hypodipsia with associated hypernatremia (12/15), tremors (6/15), and seizures (6/15). Review of the MR images revealed that 10 dogs had absence of the rostral CC and hypoplasia of the caudal portion, 4 dogs had a diffusely hypoplastic and dysplastic CC, and 1 dog had a diffusely hypoplastic CC. In 14 cases, there was abnormal cortical development with fusion of the ventral frontal lobes and part of the diencephalon, indicating lobar holoprosencephaly. Conclusions and Clinical Importance Previous literature has mainly associated CCA with adipsia and only 12 of 15 dogs in the current series demonstrated this abnormality. There are different degrees of the malformation but in 10 dogs the rostral portion of the CC is most severely affected. Fourteen dogs have simultaneous fusion of the midline structures rostral to the CC; this region has several structures involved in thirst regulation and might explain this derangement.